Pembinaan Karakter Bagi Anak-Anak Putus Sekolah Pada Program Kesetaraan Pendidikan di Kota Padang - Pratiwi, Adella Putri; Bachtiar, Yusnanik; Muchtar, Henni (Journal of Civic Education, 2023)
This study seeks to elucidate the pivotal role played by community learning activity centers in fostering character development through educational activities. Employing a descriptive qualitative approach, this research employed purposive sampling to select informants. Data was gathered through interviews, observations, and documentation, with data validity established through source triangulation. Subsequently, data underwent analysis involving reduction, presentation, and conclusion drawing. The findings of this investigation reveal that PKBM Farilla Ilmi utilizes various coaching strategies (Package A, B, and C) to guide students, including setting an example, instilling habits, offering constructive feedback, and employing a relational approach. These strategies are primarily motivated by students' spiritual needs, with observed outcomes including notable improvements in student behavior. Specifically, students exhibit enhanced discipline in meeting task deadlines and punctuality. Moreover, they display increased politeness when interacting with adults, demonstrate respect for both parents and peers, and exhibit greater honesty.